PERSEPSI MAHASISWA KEDOKTERAN TENTANG KESIAPAN MENGHADAPI KEPANITERAAN KLINIK DI RUMAH SAKIT UMUM DAERAH DELI SERDANG - KARINA ASYSYIFAA ALEMINA RAMADHANI GINTING; HEMMA YULFI (JURNAL ILMIAH KOHESI, 2021)
The first transition of medical students is when learners transfer from preclinical to clinical education. The transition coulddetermine how capable the student is and therefore motivate self evaluation, but it also may change student’s perception ordevelop new behavior. The beginning of clerkship act as “shock of practice” to medical graduate. Clerkship may cause stressand anxiety in medical students. Therefore, it is important to facilitate the student’s transition. The purpose of this study is toanalyze medical student’s perception toward their readiness to encounter clerkship at Regional Public Hospital of DeliSerdang. This is a descriptive study with cross-sectional design with point time approach. This study was conducted at thehospital on student’s of Faculty of Medicine, University of Muhammadiyah Sumatera Utara. A self-administeredquestionnaire containing 29 question, each of which illustrated the student’s perception toward preparation of enteringclerkship. The results of this study showed that majority of student’s perceived themselves ready for clinical phase at thehospital, encompassing preclinical preparation, transition, workload, patient encounter, knowledge and skills needed.Most student’s perceived good preparation to clinical phase, and the readiness was increasing incline with the length ofclinical phase they have undergone.